2021
DOI: 10.1371/journal.ppat.1010140
|View full text |Cite
|
Sign up to set email alerts
|

The Schistosoma mansoni nuclear receptor FTZ-F1 maintains esophageal gland function via transcriptional regulation of meg-8.3

Abstract: Schistosomes infect over 200 million of the world’s poorest people, but unfortunately treatment relies on a single drug. Nuclear hormone receptors are ligand-activated transcription factors that regulate diverse processes in metazoans, yet few have been functionally characterized in schistosomes. During a systematic analysis of nuclear receptor function, we found that an FTZ-F1-like receptor was essential for parasite survival. Using a combination of transcriptional profiling and chromatin immunoprecipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…MEG-24, MEG-27 and MEG-2.1 could not be produced in a heterologous host and, given their short size, they were chemically synthesized to perform in vitro studies [ 37 , 38 ]. Chemical synthesis was also employed to use peptides of several MEG proteins as baits in search for host partners; this was the case, for example, of MEG-12 [ 32 ], MEG-8 [ 39 ], and twelve other MEG proteins expressed in the tegument and esophageal glands [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…MEG-24, MEG-27 and MEG-2.1 could not be produced in a heterologous host and, given their short size, they were chemically synthesized to perform in vitro studies [ 37 , 38 ]. Chemical synthesis was also employed to use peptides of several MEG proteins as baits in search for host partners; this was the case, for example, of MEG-12 [ 32 ], MEG-8 [ 39 ], and twelve other MEG proteins expressed in the tegument and esophageal glands [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Meg-8 . 3 is only found in the esophageal gland and is required for its maintenance as well as the integrity of the head [ 108 ]. As expected, meg-8 .…”
Section: Emerging Potential Targetsmentioning
confidence: 99%
“…Another example is a nuclear receptor, Ftz-F1 , which does not appear to be expressed in the oesophageal gland, that binds to the upstream region of an oesophageal gland-specific gene, meg-8.3 (microexon gene 8.3). Interestingly, Ftz-F1 and meg-8.3 knockdowns led to degeneration of head tissue and loss of parasites’ ability to attach to the culture dish (Romero et al , 2021), highlighting the importance of individual oesophageal gland proteins in parasite homeostasis. Recent biochemical, as well as bulk and single-cell transcriptomic studies have identified several genes enriched in the gland including multiple microexon genes ( meg s), some of which have been implicated as potential vaccine candidates (Figueiredo et al , 2015; Li et al , 2015; Wilson et al , 2015; Li et al , 2018, 2020; Diaz Soria et al , 2020; Neves et al , 2020; Wendt et al , 2020).…”
Section: Digestive Systemmentioning
confidence: 99%